Pembentukan Badan Usaha Milik Desa (BUMDes) dalam Peningkatan Kesejahteraan Masyarakat di Desa Manulea, Kecamatan Sasitamen, Kabupaten Malaka - Novia Patrisia Metom; I Komang Arthana; Maria Indryani Hewe Tiwu (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study aims to describe the strategy for establishing a Village-Owned Enterprise (BUMDes) in improving the welfare of the people of Manulea Village, Sasitamean District, Malaka Regency using a SWOT analysis. The method used in the study is qualitative, aimed at obtaining data based on existing conditions, the results of direct interviews with informants and from existing documents. The results of this study indicate that the Establishment of a Village-Owned Enterprise (BUMDes) in Manulea Village has quite good potential to develop BUMDes by selecting a strategic location and close to a major road so that it becomes a special attraction to invite people from surrounding sub-districts to visit. Then the weakness of the Manulea Village community does not yet have adequate human resources to contribute to BUMDes. Next, Manulea Village has very abundant natural resources. Then the Village government strongly supports the establishment of BUMDes so that it is expected to help efforts to alleviate poverty, unemployment and improve the welfare of the Manulea Village community and the threat is that several businesses owned by the Manulea Village community are similar to the business that will be held by BUMDes. This causes internal competition for the types of businesses offered.